The issuance of the European protection order (Ius Novum, 2023)
This scientific article researches the procedure for issuing a European protection order by a Polish court or public prosecutor, resulting in the enforcement of protective, penal, or probation measures by a competent judicial or equivalent authority in a Member State of the European Union. These measures require refraining from staying in certain environments or places and avoiding contact with or proximity to certain people. This article does not cover provisions concerning the execution of such an order by the competent authority of a Member State. The main research objective is to demonstrate the importance of this measure in continuing the protection of the aggrieved in another Member State. The research findings are original and primarily national in scope but also relevant to other countries due to their relation to an EU instrument. This article analyses the essence of the European protection order, its issuance requirements, including the ruling on the aggrieved’s protection measure, necessity of issuing the order, aggrieved’s motion, issuance proceedings, authorised issuing authorities, ruling form, forum for issuance, issuance mode, right to appeal, order transmission, and information obligations. The paper is significant for its in-depth dogmatic analysis and substantial theoretical content and is practical in guiding interpretation of the requirements for the application of this measure and the issuance procedure.
Keywords: European protection order; Directive; prosecutor; court; protective measure; penal measure; preventive measure; European Union